Marathoning start to finish - Finke, P.; Finke, W.
Online-Version des Buches "Marathoning Start to Finish" mit folgenden Kapiteln: Training Principle - Marathon Physiology - Keys to Success - Base Building - Plans, Paces and Progressions - Getting Out the Door - Sharpening - Maximizing Performance - Psychological Preparation - Peaking - Race Preparation - Tapering - Planning Your Race - Racing - Final Preparations - The Race - Recovery - After Your Race - Aids to Performance - Supplimental Training - Food and Performance - Ergongenic Aids - Running in Temperature Extremes - Appendices: Example Training Log - Training Pace Tables - Example Interval Progression - Example Repeat Progression - Example Fartlek Program - Example Hill Training Progression References